Intraocular Pressure, Axial Length, and Refractive Changes after Phacoemulsification and Trabeculectomy for Open-Angle Glaucoma - Popa-Cherecheanu, Alina (2017)
Purpose. To compare changes in intraocular pressure (IOP), axial eye length (AEL), and refractive outcome in primary open-angle glaucoma patients undergoing cataract surgery and trabeculectomy in dependence of the sequence of surgeries. Materials and Methods. We retrospectively analysed 48 eyes. The changes in refraction, intraocular pressure, and axial eye length were analysed after surgery. In group A (21 subjects), phacoemulsification was performed before trabeculectomy, and in group B (27 subjects), trabeculectomy was performed before phacoemulsification with a minimum time span between interventions of 6 months. Results. The reduction in IOP and the decrease in AEL after trabeculectomy were significant after 6 and 12 months postsurgery ( p<0.001 each). The decrease in AEL was 0.42 ± 0.11% at 6 months after surgery and 0.40 ± 0.13% after 12 months from surgery; this decrease in AEL was comparable between the groups. The refractive outcome was significantly different between the groups (group A: 0.35 ± 0.75 dpt, group B: −0.05 ± 0.36 dpt, p =0.018 ); in group A, trabeculectomy caused a hyperopic shift of 0.34 ± 0.44 dpt (p = 0.002) at 12 months postsurgery. Conclusion. IOP reduction after trabeculectomy causes AEL shortening. The effect on refractive outcome depends on the sequence of surgeries. Better refractive outcome is achieved if phacoemulsification is performed after trabeculectomy.